From Unmovable Points to Structural Drift: An Introduction to Enactivism - Horn, James (European Scientific Journal, ESJ, 2018)
This essay examines possibilities for a reflexive understanding of knowledge attainment that is grounded in the enactive capacities of living systems. Appreciating the enactivist agenda requires a dislodging of obstructions created by an accumulated history of transcendental abstractions that have sought to provide a Cartesian “unmovable point” against which knowledge claims are veridically judged. This essay traces some long-held philosophical and scientific assumptions that have limited the attainment of knowledge in exchange for the banishment of epistemic anxieties that result from a loss of absolute certainty. A brief history of this problem is presented as context for the present advocacy of an enactive approach to the pursuit of cognitive outcomes. It is hoped that enactivism may offer a stable, yet evolving, understanding of how data, information, and knowledge intersect to constitute living and learning. Implications, both moral and scientific, are shared.